PERLINDUNGAN HUKUM PROFESI GURU DAN DOSEN TERHADAP PEMBERIAN IMBALAN YANG TIDAK WAJAR DALAM UNDANG-UNDANG NOMOR 14 TAHUN 2005 TENTANG GURU DAN DOSEN - Putri, Eka Elfa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Education plays an important strategic role in the effort to raise the quality of human resources. One of the most important factors in determining whether educational objectives are met is the quality of teachers. The goal of the government's move to pass Law No. 14 of 2005 on Teachers and Lecturers is to raise teacher professionalism. According to Article 41 paragraph 3 of Law No. 14 of 2005, members of professional organizations are required to be teachers. According to Article 42, letter c, teachers are required to adhere to the professional code of ethics that is overseen by the Teacher Honor Council. They can fight for their rights to professional protection through professional organizations. According to Law No. 14 of 2005 Concerning Private Teachers and Lecturers in Part Seven of Article 39 paragraph (4), the government guarantees teachers' rights to obtain professional protection. However, teachers actually face financial challenges in order to survive. In Indonesia, prospective teachers may be put at risk and discouraged if the salaries that teachers receive are too high and do not increase in number. The conclusion reached is that a teacher should be able to receive an unfair reward for his or her work, but some of it is not even given to the teacher in question. As a matter of fact, on the off chance that a sensible gift is given to the instructor, the educator can be utilized for: making existing teachers feel at ease and content, attracting qualified individuals, and encouraging teachers to teach. Preventive and repressive legal protection is the type of professional legal protection available to lecturers and teachers